1973
DOI: 10.1111/j.1476-5381.1973.tb08534.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cannabinoids on intestinal motility and their antinociceptive effect in mice

Abstract: Summary1. After oral administration to mice, pethidine, A8-tetrahydrocannabinol (THC), A9-THC, a cannabis extract and cannabinol had a dose-dependent antinociceptive effect when measured by the hot-plate method. Cannabidiol was inactive at 30 mg/kg. A8-THC, A9-THC and pethidine did not differ significantly in potency, but A9-THC was 6 5 times more active than cannabinol. 2. After oral administration, three different cannabis extracts, A8-THC, A9-THC and morphine produced dose-dependent depressions of the passa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 8 publications
3
59
0
Order By: Relevance
“…It has been reported that cannabinoids may reduce intestinal motility in rodents (Chesher et al, 1973). There was a delay in ethanol and pentobarbitone absorption in some volunteers who received delta-9-tetrahydrocannabinol for 14 days in high doses, but this was not a universal effect (Benowitz & Jones, 1977).…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that cannabinoids may reduce intestinal motility in rodents (Chesher et al, 1973). There was a delay in ethanol and pentobarbitone absorption in some volunteers who received delta-9-tetrahydrocannabinol for 14 days in high doses, but this was not a universal effect (Benowitz & Jones, 1977).…”
Section: Discussionmentioning
confidence: 96%
“…A fu rther difference from morphine is that cannabinoid inhibition of intestinal motility is not antago nized by nalophine (189).…”
Section: Tolerance and Withdrawal Effectsmentioning
confidence: 99%
“…Specifically in mouse experiments, THC significantly decreased the response latencies to heat stimuli (hot plate, tail flick; Martin and Lichtman, 1998). This was interpreted as indicating antinociceptive effects on a sensory level (Bloom and Dewey, 1978;Chesher et al, 1973), which would further agree with cannabinoid receptors being present in pain circuits from the peripheral sensory nerve endings up to the brain (Manzanares et al, 2006). Endocannabinoids are also involved in endogenous pain inhibition (Walker et al, 2001), as shown in models of chronic inflammatory and neuropathic pain (Agarwal et al, 2007;Bishay et al, 2010).…”
Section: Intrinsic Connections (A Parameter)mentioning
confidence: 99%